Effective Use of ICT in Enhancing Classroom Learning Experiences - Latuconsina, Adam; Al-Momani, Ammar; Khatib, Rania (Journal International Inspire Education Technology, 2025)
The integration of Information and Communication Technology (ICT) in education has transformed traditional classroom learning, offering new opportunities for engagement, interactivity, and personalized instruction. Despite the increasing adoption of digital tools in education, their effective implementation remains a challenge due to varying levels of digital literacy, resource availability, and pedagogical integration. Ensuring the optimal use of ICT in classrooms is essential for enhancing student engagement and improving learning outcomes. This study aims to examine the effectiveness of ICT in enriching classroom learning experiences by evaluating its impact on student participation, knowledge retention, and instructional efficiency. A mixed-methods approach was employed, incorporating surveys, classroom observations, and instructor interviews to assess ICT implementation across various educational settings. Findings indicate that interactive learning technologies, adaptive digital content, and real-time feedback mechanisms significantly enhance student motivation and comprehension. Statistical analysis revealed a strong correlation between structured ICT integration and academic performance. The study concludes that a well-planned and pedagogically informed use of ICT fosters a more interactive and engaging learning environment. Future research should explore long-term impacts of ICT in education and the development of frameworks for more inclusive and scalable technology integration in diverse classroom contexts.